PREVALENCE OF TOOTH INVOLVED (PERIO-ENDO) LESION AMONG DUHOK POPULATION: ACROSS SECTIONAL STUDY - QASIM, HUDA JMEEL; KARAM, BANGEN MOHAMMED; MOUSA, HASHIM DAWOOD; MOHAMMED, SAEED ALI (Journal of Duhok University, 2023)
Background: The lesions brought on by inflammatory substances that are to varied degrees present in both the periodontium and the pulpal tissues have been referred to as "perio-endo" lesions. The aim of the study was to determine the prevalence of perio-endo lesion in Duhok province from 2021 to 2022. Materials and methods: Screening of a total of 821 patients was performed whom reported with periodontal diseases. Complete demographic details of all the patients were obtained. Clinical examination was carried out for all the patients. Both periodontal and pulpal examination was completed through utilizing mouth mirror, UNC-type periodontal and explorer probes with the aid of periapical and panoramic radiographs and vitality test (particularly for the non-carious teeth). A Performa was made and final diagnosis and possible etiological factor along with complete history of present illness was recorded. All the results were recorded in Microsoft excel sheet and were analyzed through using SPSS software. Results: Out of the total 821 periodontally involved patients, Perio-Endo lesions were found in 15.34% of the patients. Among all diagnosed Perio-Endo lesion cases, lower teeth involvement occurred in 47.6%, molar teeth were the most commonly involved with Perio-Endo lesions and found in 46%, premolars were involved in 29.4%. Conclusion: In Duhok province a significant proportion of the patients are affected by Perio-Endo lesions